2018
DOI: 10.21037/atm.2018.02.26
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar disc reherniation after transforaminal lumbar endoscopic discectomy

Abstract: Transforaminal endoscopic surgical access to lumbar disc herniations is an ultra-minimally invasive approach for the treatment lumbar degenerative disc disease. It allows for neural decompression by removing disc and foraminal pathology with minimal bone removal. This minimal bone removal prevents iatrogenic destabilization. However, the 1-year reherniation rate presented here is 4.7%. This suggests that the benefit of this technique may be that it is ultra-minimally invasive, but it may only be equal, not sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…There was one patient (4.3%) occurred recurrent disc herniation in this study, it was within microdiscectomy reherniation rates range from 2.3% to 11.8% (26). The recurrent disc herniation rate experienced in this study was similar to Kosztowski et al's reherniation rates of 4.76% after transforaminal lumbar endoscopic discectomy (18).…”
Section: The Feasibility Advantages and Disadvantages Of The Modifiesupporting
confidence: 84%
See 2 more Smart Citations
“…There was one patient (4.3%) occurred recurrent disc herniation in this study, it was within microdiscectomy reherniation rates range from 2.3% to 11.8% (26). The recurrent disc herniation rate experienced in this study was similar to Kosztowski et al's reherniation rates of 4.76% after transforaminal lumbar endoscopic discectomy (18).…”
Section: The Feasibility Advantages and Disadvantages Of The Modifiesupporting
confidence: 84%
“…Even though TESSYS is a minimal invasive technique, some complications are unavoidable in the surgeries. Literatures reported that an incidence of 1% in sensory deficits, 10% in dysesthesias, and 0.3% in dural tears respectively occurred in TESSYS surgeries (18,26). Any operation contacts nerve root might injure nerve tissues intraoperatively, but with local anesthesia, patient could immediately complain any pain or numbness in case of neurostimulus.…”
Section: The Feasibility Advantages and Disadvantages Of The Modifiementioning
confidence: 99%
See 1 more Smart Citation
“…At present, surgery is a common method of LDH treatment, but traditional open surgery has many shortcomings, such as large incision, large intraoperative hemorrhage, slow postoperative recovery and many other complications (18). In nearly 10 years, spine minimally invasive surgery has developed rapidly, and LDH surgical treatment has developed from traditional open surgery to minimally invasive surgery (19). However, the prognosis of LDH patients varies with different operations.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar intervertebral disc herniation is a common spinal disease. The principle of operative treatment is to relieve mechanical compression of the roots or the cord while guarantying spine integrity and mechanical stability to the greatest degree 4,5 Open operation often requires stripping many muscles beside lumbar vertebra, cutting ligamentum flavum open, destroying vertebral plate and zygapophyseal joint, pulling nerve root and dural sac and causing damage to bony structure of centrum. These operative techniques may adversely affect the stability of the spine.…”
Section: Discussionmentioning
confidence: 99%